p (x) = x² 3x+2 ka answer
Attachments:
![](https://hi-static.z-dn.net/files/db7/6bcb85f0f819d7ceed2a52fdc7e5ab78.jpg)
Answers
Answered by
3
Answer:
1-3×1+2 4²+13×4+2=16+52 2 =72
1-3+2
3-3
0
Step-by-step explanation:
P(1) =4×1²+13×1+9 =4+13+9=26
P(4)=4×4²+13×4+9=64+52+9
=106+9
115
IF YOU LIKE MY ANSWER THEN FOLLOW ME
Answered by
16
p(x)= x²- 3x+2
p(x)= x²- 3x+2
p(1)= 1²- 3(1)+2.
⠀⠀⠀ =1 - 3+2
⠀⠀⠀= -2+2
⠀⠀⠀ = 0
p(x)= x²- 3x+2
p(4)= 4²- 3(4)+2.
⠀⠀⠀⠀=16 - 12+2
⠀⠀⠀⠀= 4+2
⠀⠀⠀⠀= 6
Similar questions
English,
4 months ago
Social Sciences,
4 months ago
Social Sciences,
4 months ago
Science,
9 months ago
Physics,
9 months ago
English,
1 year ago
English,
1 year ago
Science,
1 year ago